2017
DOI: 10.1002/hep.28874
|View full text |Cite
|
Sign up to set email alerts
|

IL‐6 trans‐signaling is essential for the development of hepatocellular carcinoma in mice

Abstract: Hepatocellular carcinoma (HCC) is one of the most frequent tumors worldwide with rising incidence. The inflammatory cytokine, interleukin‐6 (IL‐6), is a critical mediator of HCC development. It can signal through two distinct pathways: the IL‐6 classic and the IL‐6 trans‐signaling pathway. Whereas IL‐6 classic signaling is important for innate and acquired immunity, IL‐6 trans‐signaling has been linked to accelerated liver regeneration and several chronic inflammatory pathologies. However, its implication in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 41 publications
4
123
0
3
Order By: Relevance
“…We analyzed the microarray data to identify the downstream targets responsible for the biological functions of hPCL3s (Supplementary Table S3). The expression of IL6, which was previously shown to be a driver of HCC (20), was dramatically upregulated upon hPCL3s overexpression in PVTT cells. Consistent with the microarray data, the forced expression of hPCL3s in Hep3B and PVTT cells increased the expression of the IL6 mRNA, whereas hPCL3s knockdown decreased the expression of the IL6 mRNA in PVTT and Huh7 cells ( Fig.…”
Section: Il6 Was a Target Gene Downstream Of Hpcl3s/b-catenin/tcf Sigmentioning
confidence: 79%
“…We analyzed the microarray data to identify the downstream targets responsible for the biological functions of hPCL3s (Supplementary Table S3). The expression of IL6, which was previously shown to be a driver of HCC (20), was dramatically upregulated upon hPCL3s overexpression in PVTT cells. Consistent with the microarray data, the forced expression of hPCL3s in Hep3B and PVTT cells increased the expression of the IL6 mRNA, whereas hPCL3s knockdown decreased the expression of the IL6 mRNA in PVTT and Huh7 cells ( Fig.…”
Section: Il6 Was a Target Gene Downstream Of Hpcl3s/b-catenin/tcf Sigmentioning
confidence: 79%
“…Proinflammatory cytokine IL-6 is a primary cytokine in the tumor microenvironment, which is produced by macrophages, neutrophils, monocytes, tumor cells and other cell types [38][39][40]. IL-6 has been demonstrated to promote the invasion of blood vessels by cancer cells through its role as an important trigger of EMT [41].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that increased activity of meprin β on the cell surface reduced cell proliferation. Another pathway influenced by ADAM17, emerging in different tumor entities, is interleukin 6 (IL-6) and IL-6R-induced trans-signaling (Bergmann et al, 2017;Schmidt et al, 2018). Here, ADAM17 releases the IL-6R from the cell surface of one cell, and then this soluble receptor forms a signaling complex together with its cytokine and gp130 (also known as IL6ST) on another cell to induce cell survival via STAT3 phosphorylation (Schaper and Rose-John, 2015).…”
Section: Discussionmentioning
confidence: 99%